Mechanisms regulating nutrition-dependent developmental plasticity through organ-specific effects in insects - Koyama, Takashi; Mendes, Cláudia; Mirth, Christen K. (Frontiers in Physiology, 2013)
Nutrition, via the insulin/insulin-like growth factor (IIS)/Target of Rapamycin (TOR) signaling pathway, can provide a strong molding force for determining animal size and shape. For instance, nutrition induces a disproportionate increase in the size of male horns in dung and rhinoceros beetles, or mandibles in staghorn or horned flour beetles, relative to body size. In these species, well-fed male larvae produce adults with greatly enlarged horns or mandibles, whereas males that are starved or poorly fed as larvae bear much more modest appendages. Changes in IIS/TOR signaling plays a key role in appendage development by regulating growth in the horn and mandible primordia. In contrast, changes the IIS/TOR pathway produces minimal effects on the size of other adult structures, such as the male genitalia in fruit flies and dung beetles. The horn, mandible and genitalia illustrate that although all tissues are exposed to the same hormonal environment within the larval body, the extent to which insulin can induce growth is organ specific. In addition, the IIS/TOR pathway affects body size and shape by controlling production of metamorphic hormones important for regulating developmental timing, like the steroid molting hormone ecdysone and sesquiterpenoid hormone juvenile hormone. In this review, we discuss recent results from Drosophila and other insects that highlight mechanisms allowing tissues to differ in their sensitivity to IIS/TOR and the potential consequences of these differences on body size and shape.